Editing activity for eliminating mischarged tRNAs is essential in mammalian mitochondria - Hilander T; Zhou XL; Konovalova S; Zhang FP; Euro L; Chilov D; Poutanen M; Chihade J; Wang ED; Tyynismaa H (OXFORD UNIV PRESS, 2025)
Accuracy of protein synthesis is enabled by the selection of amino acids for tRNA charging by aminoacyl-tRNA synthetases (ARSs), and further enhanced by the proofreading functions of some of these enzymes for eliminating tRNAs mischarged with noncognate amino acids. Mouse models of editing-defective cytoplasmic alanyl-tRNA synthetase (AlaRS) have previously demonstrated the importance of proofreading for cytoplasmic protein synthesis, with embryonic lethal and progressive neurodegeneration phenotypes. Mammalian mitochondria import their own set of nuclear-encoded ARSs for translating critical polypeptides of the oxidative phosphorylation system, but the importance of editing by the mitochondrial ARSs for mitochondrial proteostasis has not been known. We demonstrate here that the human mitochondrial AlaRS is capable of editing mischarged tRNAs in vitro, and that loss of the proofreading activity causes embryonic lethality in mice. These results indicate that tRNA proofreading is essential in mammalian mitochondria, and cannot be overcome by other quality control mechanisms.